2017
DOI: 10.1080/15614263.2017.1405265
|View full text |Cite
|
Sign up to set email alerts
|

Can community policing increase residents’ informal social control? Testing the impact of the Chicago Alternative Policing Strategy

Abstract: This study examines whether community policing can build informal social control.Specifically, this paper assesses the impact of the Chicago Alternative Policing Strategy (CAPS) in Chicago neighborhoods. The data for this research are drawn from both the Community Survey of the Project on Human Development in Chicago Neighborhoods (PHDCN) and the CAPS Prototype Panel Survey. Bivariate and multivariate methods are used to analyze data gathered from 8,782 residents nested within 343 neighborhood clusters. Ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…community engagement and police presence) and collective efficacy. Furthermore, two of the three field experiments testing the impact of a community policing intervention found significant and positive effects on collective efficacy (Kochel and Weisburd, 2019;Lombardo and Donner, 2018). There is a relative scarcity of policing field experiments that use collective efficacy as an outcome measure, compared with other outcomes, such as crime, perceived disorder, fear of crime, citizen satisfaction and legitimacy of police (Braga et al, 2019;Gill et al, 2014;Hinkle et al, 2020;Mazerolle, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…community engagement and police presence) and collective efficacy. Furthermore, two of the three field experiments testing the impact of a community policing intervention found significant and positive effects on collective efficacy (Kochel and Weisburd, 2019;Lombardo and Donner, 2018). There is a relative scarcity of policing field experiments that use collective efficacy as an outcome measure, compared with other outcomes, such as crime, perceived disorder, fear of crime, citizen satisfaction and legitimacy of police (Braga et al, 2019;Gill et al, 2014;Hinkle et al, 2020;Mazerolle, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these measures, five field experiments tested the effect of a policing intervention on collective efficacy. Of the policing interventions tested, three were of some form of community policing intervention (Kochel and Weisburd, 2019;Lombardo and Donner, 2018;Tuffin et al, 2006), one was of an intervention specifically designed to increase collective action and collective efficacy (Weisburd et al, 2020), and one was of a broken windows style intervention (Weisburd et al, 2011).…”
Section: Measurement Of Key Constructsmentioning
confidence: 99%
“…Despite how promising this sounds, it is now widely recognized that community policing has been generally unsuccessful. Initially positive effects found by Lombardo and Donner (2018) were accounted for primarily by the level of community disorganization and the existing level of satisfaction of community members with the police. Gill, Weisburd, Telep, Vitter, and Bennett (2014) found that community policing increased citizen satisfaction and ratings of disorder but did not reduce crime or fear of crime.…”
Section: Community Alternatives For Policingmentioning
confidence: 99%
“…In a recent study, researchers analyzed the impact of bicycle and motorized patrols in Canada, concluding that bicycle patrols are more proactive in the context of community-oriented policing (Sytsma and Piza, 2018). In another study, researchers from the Department of Criminal Justice and Criminology at Loyola University Chicago assessed the community policing effect on informal social control in Chicago neighborhoods (Lombardo and Donner, 2018; Xu et al, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%